New Methodology in Interpretation of Aeromagnetic Anomalies over Pipe-Like Sources using Analytic Signal Ratio Approach - Vappangi, Pradeep Kumar; Kasturi, Naganjaneyulu (Trends in Sciences, 2022)
Concepts of signal processing like Fourier transform, filtering, power spectrum, derivatives etc., are widely used in geophysical models in exploring the Earth structures. For example, quantitative interpretation of aeromagnetic maps is based mainly on choosing an appropriate model for evaluating parameters of the causative source. For circular or elliptical anomalies caused by plug-like intrusive sources, the vertical pipe of infinite depth extent (also known as single or mono pole) is most suited. It is also more common to use analytic signal maps in interpretation. For a vertical pipe, the total magnetic intensity (TMI) anomaly is anti-symmetric at the magnetic equator and progressively becomes symmetric at the pole. Based on this property, a new methodology is developed for identifying location and depth of magnetic structures beneath. It is concluded that the analytic signal is almost symmetric for any magnetic latitude and by using both the properties of the anomaly and its analytic signal the location and depth can be evaluated. This new approach is validated by field examples. HIGHLIGHTS The theory and application of using analytic signal to determine the location and depth to the point pole is described The method is useful in locating pipe-like (vertical cylinder, kimberlite pipes) structures The shape of the magnetic anomaly changes with magnetic inclination whereas the analytic signal map is symmetric and almost circular, with its maximum centred over the top of the pipe The analytic signal is almost symmetric for any magnetic latitude and by using both the properties of the anomaly and its analytic signal, the location and depth to the top can be evaluated GRAPHICAL ABSTRACT